The Star, 20 March 2007 (Star Publications (Malaysia) Berhad, 2007)
Seventeen student aged between 14 and 18 recently completed in three gruelling debates for the chance to be part of a five -member team that will represent the coutry at the world school Debating Championship 2007 from July 2 to 12 in Seoul, south Korea.